2018
DOI: 10.31031/rmes.2018.04.000597
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Risk Factors of Lumbar Intervertebral Disc (IVD) Degeneration

Abstract: Biological factors (Table 1) Changes in ECM (Extracellular Matrix): Collagen synthesis increases in the initial stages of degeneration with a clear increase in type II Collagen in the NP (maybe indicating repair mechanism) [9]. As the degeneration progresses the synthesis pattern changes and more type II Collagen is synthesized in AF. Type I collagen is synthesized in the deep region of AF and NP. Type X collagen formation is associated with chondrocyte agglomerates and tears of degenerated IVDs. The synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
0
7
0
1
Order By: Relevance
“…Various factors, including mechanical influences, environmental factors, occupational exposures, traumatic injuries, smoking, and changes related to aging, have been implicated in the etiopathogenesis of disc degeneration. 12,13 Inflammation of the disc tissue plays a significant role in the process of accelerated disc degeneration. [14][15][16] Genetic factors are increasingly proven; whereas, environmental factors are relatively less important.…”
Section: Discussionmentioning
confidence: 99%
“…Various factors, including mechanical influences, environmental factors, occupational exposures, traumatic injuries, smoking, and changes related to aging, have been implicated in the etiopathogenesis of disc degeneration. 12,13 Inflammation of the disc tissue plays a significant role in the process of accelerated disc degeneration. [14][15][16] Genetic factors are increasingly proven; whereas, environmental factors are relatively less important.…”
Section: Discussionmentioning
confidence: 99%
“…В то же время, хотя симптомная дегенерация МПД считается распространенной причиной неспецифической боли в спине, этиология и патофизиологические механизмы, лежащие в основе дегенеративного процесса, остаются недостаточно понятными, как и связь между дегенерацией диска, дискогенной болью и грыжей диска [28,29].…”
Section: этиопатогенетические механизмы дегенерации мпдunclassified
“…According to the study conducted by [8] it showed that the prevalence of LDH is greater in adults compared to children and adolescents. Genetic factors have been identified as the primary cause of the majority of instances with LDH.…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive activities or occupations that place a significant amount of stress on the lower back can increase the risk of disc herniation. This includes heavy lifting, prolonged sitting or repetitive bending and twisting movements [8]. Being overweight or leading a sedentary lifestyle can contribute to the risk of lumbar disc herniation (LDH).…”
Section: Introductionmentioning
confidence: 99%